THE EFFECTIVE TAX POLICY AND DEVELOPMENT OF SMALL BUSINESS - ALTERNATIVE WAYS OF INTERACTION - Dana Manarkyzy, Тұрлыбек (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article presents the data describing the possibility of the tax system in terms of support for small and medium businesses. The data on the international experience to support the small and medium business, approaches to tax policy of the Republic of Kazakhstan, which is characterized by the presence of special tax regimes is provided. The possibility of additional tax stimulation of small and medium businesses through direct tax incentives and the provision of them to credit financial institutions is indicated